EFEKTIVITAS METODE PEMBELAJARAN TUTOR SEBAYA TERHADAP HASIL BELAJAR PADA ELEMEN RENCANA BIAYA DAN PENJADWALAN KONSTRUKSI BANGUNAN DI SMK NEGERI 1 PARIAMAN - Shintya Athala Marza; Nidal Zuwida (Unversitas Negeri Padang, 2024)
Teachers cannot reach all the students in the class. This results in a significant difference in value between the most intelligent and least intelligent students on elements of Cost Planning and Building Construction Scheduling. This difference in scores is a factor in selecting peer teaching learning methods. This research was conducted to determine how effective peer teaching to improving student learning results in elements of Cost Planning and Building Construction Scheduling. The type of research used is experimental research with a non-equivalent pretest posttest control group design model. The number of samples used was 36 people: 18 students of class XI DPIB 1 who acted for the control class and 18 students of class XI DPIB 2 who acted for the experimental class. The experimental class uses a peer tutor teaching approach. The research was conducted by providing test instruments in the form of a pretest and posttest which were first tested on 26 class XI students of SMK Negeri 1 West Sumatra. The average of student learning results in the experimental class was 92.17 and the control class was 47.89. Student learning results appear to be better than the average comparison of the two classes in this study. Hypothesis testing used the Mann Whitney U-Test which found that Asymp.Sig < 0.05 and 0.000 < 0.05. So, from hypothesis testing it is stated that peer teaching is effective in improving student learning results in the Elements of Cost Planning and Building Construction Scheduling.